To find an expression equivalent to \((z + 4)(z - 4)\), we can use the difference of squares formula, which states:
\[ (a + b)(a - b) = a^2 - b^2 \]
In this case, \(a = z\) and \(b = 4\). Therefore, we can apply the formula as follows:
\[ (z + 4)(z - 4) = z^2 - 4^2 \] \[ = z^2 - 16 \]
So, the expression equivalent to \((z + 4)(z - 4)\) is:
\[ z^2 - 16 \]
None of the responses provided directly state \(z^2 - 16\) as an option, but we can see that it is the difference of squares and can be properly simplified. It appears that responses may be presented in a confusing way, but the equivalent expression you are looking for is:
\(z^2 - 16\).